2019
DOI: 10.1016/j.vaccine.2018.01.060
|View full text |Cite
|
Sign up to set email alerts
|

National immunization strategies targeting migrants in six European countries

Abstract: Over the last three years an unprecedented flow of migrants arrived in Europe. There is evidence that vaccine preventable diseases have caused outbreaks in migrant holding centres. These outbreaks can be favored by a combination of factors including low immunization coverage, bad conditions that migrants face during their exhausting journey and overcrowding within holding facilities. In 2017, we conducted an online survey in Croatia, Greece, Italy, Malta, Portugal and Slovenia to explore the national immunizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 14 publications
1
20
0
2
Order By: Relevance
“…Migrants, refugees, and international travelers may import diseases, and outbreaks may occur (Chen et al, 2010;Nakken et al, 2018). There is a need to develop strategies to facilitate and monitor such individuals at high risk of developing infectious diseases, and provide access to vaccinations (Kinsman et al, 2018;Giambi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Migrants, refugees, and international travelers may import diseases, and outbreaks may occur (Chen et al, 2010;Nakken et al, 2018). There is a need to develop strategies to facilitate and monitor such individuals at high risk of developing infectious diseases, and provide access to vaccinations (Kinsman et al, 2018;Giambi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that diseases that can be prevented by vaccination cause flare-ups in reception and holding centers [39,42,43,44,45,46,47,48]. Outbreaks are generally more severe in refugee camps [48].…”
Section: Health Problems Facing Refugeesmentioning
confidence: 99%
“…It was demonstrated that diseases that can be prevented by vaccination cause flare-ups in reception and holding centers [39,42,43,44,45,46,47,48]. Outbreaks are generally more severe in refugee camps [48]. Sharing dormitories, a lack of accessible toilet facilities, poor hygiene conditions, undernourishment, and limited access to medical care were reported as factors contributing to the increased susceptibility to disease [35,49].…”
Section: Health Problems Facing Refugeesmentioning
confidence: 99%
See 2 more Smart Citations